THE EFFECT OF WORK DISCIPLINE ON MEDICAL MEDICAL EMPLOYEE PERFORMANCE WITH WORK COMMUNICATION AS AN INTERVENING VARIABLE (Case Study of Serdang Bedagai Hospital Centre Sultan Sulaiman Hospital) - Stephen Martin; Bob Feinberg (PT. Radja Intercontinental Publishing, 2023)
The results of this study show. (1) It can be seen that the value of the adjusted R square is 0.046 or 04.6%. This shows that work discipline (X) can explain work communication (Z) by 04.6%, the remaining 95.4% (100% - 04.6%) is explained by other variables outside this research model. (2) The results of the (Partial) t test can be seen that a tcount value of 1.544 is obtained with α = 5%, ttable (5%; nk = 28) obtained a ttable value of 2.048. From this description it can be seen that tcount (1.544) < ttable ( 2.048), as well as the significance value of 0.134 > 0.05, it can be concluded that the first hypothesis is rejected, meaning that the work discipline variable (X) has no positive and significant effect on work communication (Z). (3) The results of the t test (Partial) can be seen that the value of tcount is 0, 078 With α = 5%, ttable (5%; nk = 28) obtained a ttable value of 2.048 From this description it can be seen that tcount (0.078) < ttable (2.048), and its significance value is 0.938 > 0.05, it can be concluded that the hypothesis the third is rejected, meaning that work communication (Z) has no significant effect on MEDICAL EMPLOYEE PERFORMANCE (Y). (4) Path analysis shows the direct effect of variable X on variable Y of 0.676. While the indirect effect through variable Z is 0.280 x 0.012 = 0.003, the results of the calculations show that the indirect effect through variable Z is smaller than the direct effect on variable Y. and a significance value of 0.938 > 0.05, it can be concluded that the third hypothesis is rejected, meaning that work communication (Z) has no significant effect on MEDICAL EMPLOYEE PERFORMANCE (Y). (4) Path analysis shows the direct effect of variable X on variable Y of 0.676. While the indirect effect through variable Z is 0.280 x 0.012 = 0.003, the results of the calculations show that the indirect effect through variable Z is smaller than the direct effect on variable Y. and a significance value of 0.938 > 0.05, it can be concluded that the third hypothesis is rejected, meaning that work communication (Z) has no significant effect on MEDICAL EMPLOYEE PERFORMANCE (Y). (4) Path analysis shows the direct effect of variable X on variable Y of 0.676. While the indirect effect through variable Z is 0.280 x 0.012 = 0.003, the results of the calculations show that the indirect effect through variable Z is smaller than the direct effect on variable Y.